Respuesta :

Space

Answer:

[tex]\boxed{k = \frac{L^2 + p}{4t}}[/tex]

General Formulas and Concepts:

Algebra I

Basic Equality Properties

  1. Multiplication Property of Equality
  2. Division Property of Equality
  3. Addition Property of Equality
  4. Subtraction Property of Equality

Step-by-step explanation:

Step 1: Define

Identify given.

[tex]\displaystyle L = \sqrt{4kt - p}[/tex]

Step 2: Solve for k
We can use equality properties to help us rewrite the equation to get k as our subject:

Let's first square both sides:

[tex]\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow L^2 = \big( \sqrt{4kt - p} \big) ^2 \\& \rightarrow L^2 = 4kt - p \\\end{aligned}[/tex]

Next, add p to both sides:

[tex]\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow L^2 = \big( \sqrt{4kt - p} \big) ^2 \\& \rightarrow L^2 = 4kt - p \\& \rightarrow L^2 + p = 4kt \\\end{aligned}[/tex]

Next, divide 4t by both sides:

[tex]\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow L^2 = \big( \sqrt{4kt - p} \big) ^2 \\& \rightarrow L^2 = 4kt - p \\& \rightarrow L^2 + p = 4kt \\& \rightarrow \frac{L^2 + p}{4t} = k \\\end{aligned}[/tex]

We can rewrite the new equation by swapping sides to obtain our final expression:

[tex]\displaystyle\begin{aligned}L = \sqrt{4kt - p} & \rightarrow \boxed{k = \frac{L^2 + p}{4t}}\end{aligned}[/tex]

∴ we have changed the subject of the formula.

---

Learn more about Algebra I: https://brainly.com/question/27698547

---

Topic: Algebra I

ACCESS MORE